Super-amphiphobic carbon nanotube epoxy powder coating as well as preparation method and application thereof

A super-amphiphobic carbon nanotube epoxy powder coating, prepared with modified carbon nanotubes and epoxy resin, addresses durability and process complexity issues, offering robust anti-corrosion and weather-resistant performance.

CN119242132APending Publication Date: 2025-01-03SOUTH CHINA UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411439236.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing superamphiphobic surfaces have poor durability and complex preparation processes, hindering their practical application in complex environments.

Method used

A super-amphiphobic carbon nanotube epoxy powder coating is prepared by mixing epoxy resin, super-amphiphobic carbon nanotubes, curing agents, pigments, and fillers, followed by electrostatic spraying and curing, utilizing carbon nanotubes modified with silicon dioxide and fluorosilane to achieve low surface energy and stability.

Benefits of technology

The coating exhibits excellent weather resistance, wear resistance, and anti-corrosion performance, maintaining super-amphiphobic properties under UV radiation and harsh environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005085912600000011
    Figure HDA0005085912600000011
  • Figure HDA0005085912600000012
    Figure HDA0005085912600000012
  • Figure HDA0005085912600000021
    Figure HDA0005085912600000021
Patent Text Reader

Abstract

The invention discloses a super-amphiphobic carbon nanotube epoxy powder coating as well as a preparation method and application thereof. The super-amphiphobic carbon nanotube epoxy powder coating is prepared from the following raw material components in parts by mass: 80-120 parts of epoxy resin; 1 part to 50 parts of a super-amphiphobic carbon nano tube; 10 to 50 parts of a curing agent; 10 to 100 parts of pigment and filler; 2 to 20 parts of an auxiliary agent; the super-amphiphobic carbon nano tube is prepared by loading silicon dioxide on a carbon nano tube and then modifying the carbon nano tube with fluorosilane. The water contact angle and the oil contact angle of the super-amphiphobic carbon nano tube epoxy powder coating both exceed 150 degrees, and the super-amphiphobic carbon nano tube epoxy powder coating shows super-amphiphobic performance. Besides, a salt spray test, an outdoor exposure test, an ultraviolet accelerated weather resistance test and a wear resistance test show that the obtained super-amphiphobic carbon nano tube epoxy powder coating has excellent corrosion resistance, weather resistance and wear resistance, and results show that the super-amphiphobic carbon nano tube epoxy powder coating can achieve more excellent and longer-acting multifunctional protection performance on the steel structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a super-amphiphobic carbon nanotube epoxy powder coating and a preparation method and application thereof. Background Art

[0002] Superamphiphobic surfaces have been widely studied in the past few years. By simulating the microvilli structure of the lotus leaf surface and modifying the surface with low surface energy, the contact area between liquid and solid can be significantly reduced. Superamphiphobic surfaces have been widely used in self-cleaning, anti-icing, oil-water separation, anti-fouling, and anti-corrosion. However, most superamphiphobic surfaces have poor durability and complex preparation processes, which seriously hinder their practical application in complex environments.

[0003] As a two-dimensional carbon nanofiller, carbon nanotubes have a huge specific surface area and can effectively block the diffusion of corrosive media in the coating. In addition, carbon nanotubes can also be used as grafts or loads of various functional groups, which can effectively carry out low surface energy modification and nanostructure construction. Summary of the invention

[0004] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention aims to provide a super-amphiphobic carbon nanotube epoxy powder coating and a preparation method and application thereof.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect of the present invention, a super-amphiphobic carbon nanotube epoxy powder coating is provided, wherein the raw materials for its preparation include the following components in parts by mass:

[0007] Epoxy resin: 80 to 120 parts;

[0008] Super amphiphobic carbon nanotubes: 1 to 50 parts;

[0009] Curing agent: 10 to 50 parts;

[0010] Pigments and fillers: 10 to 100 parts;

[0011] Additives: 2 to 20 parts;

[0012] The super-amphiphobic carbon nanotubes include carbon nanotubes loaded with silicon dioxide and then modified with fluorosilane.

[0013] In some embodiments of the present invention, the super-amphiphobic carbon nanotube epoxy powder coating comprises the following components in parts by mass:

[0014] Epoxy resin: 100 parts;

[0015] Super amphiphobic carbon nanotubes: 1 to 50 parts; such as 5 parts, 10 parts, 20 parts, 30 parts, 35 parts, 40 parts, 45 parts, etc.;

[0016] Curing agent: 10 to 50 parts; such as 5 parts, 20 parts, 30 parts, 35 parts, 40 parts, 45 parts, etc.;

[0017] Pigments and fillers: 10 to 100 parts; such as 5, 20, 30, 35, 40, 45, 50, 60, 70, 80, 90, etc.

[0018] Additives: 2 to 20 parts; such as 5 parts, 7 parts, 9 parts, 10 parts, 13 parts, 15 parts, 17 parts, 18 parts, 19 parts, etc.

[0019] In some embodiments of the present invention, the super-amphiphobic carbon nanotubes are prepared by mixing hydroxylated carbon nanotubes with a silicon source and then subjecting the mixture to a fluorosilane modification treatment.

[0020] In some embodiments of the present invention, the super-amphiphobic carbon nanotubes include dispersing carbon nanotubes in an ethanol solution, adjusting the pH to 12-14, adding a silicon source and mixing to obtain SiO2-CNT composite particles; then dispersing the SiO2-CNT composite particles into a mixed solution of water and ethanol, and then mixing with fluorosilane to obtain super-amphiphobic carbon nanotubes.

[0021] In some embodiments of the present invention, the silicon source is at least one of ethyl silicate (TEOS), methyltrimethoxysilane (MTMS), ethyltrimethoxysilane (MTES), ethyltriethoxysilane (ETEOS), and sodium silicate.

[0022] In some embodiments of the present invention, the fluorosilane includes at least one of perfluorooctyltrimethoxysilane, perfluorooctyltriethoxysilane and perfluorododecyltrimethoxysilane.

[0023] In some embodiments of the present invention, the epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin.

[0024] In some embodiments of the present invention, the curing agent is at least one of a dicyandiamide curing agent, a phenol curing agent, and an acid anhydride curing agent.

[0025] In some embodiments of the present invention, the pigment filler is selected from at least one of titanium dioxide, barium sulfate powder, wollastonite powder, and mica powder.

[0026] In some embodiments of the present invention, the auxiliary agent is selected from at least one of a brightener, a leveling agent, a degassing agent, an antioxidant, an ultraviolet light absorber, a light stabilizer, and an adhesion promoter.

[0027] In some embodiments of the present invention, most of the brightener compounds are derivatives of stilbene or 4,4'-diaminostilbene, biphenyl, five-membered heterocycles (triazole, oxazole, imidazole, etc.) or six-membered heterocycles (coumarin, naphthamide, triazine, etc.); such as derivatives of bis(triazine)amino-stilbene; bisacylamino derivatives of stilbene; triazole derivatives of stilbene; oxadiazole derivatives of stilbene; oxazole derivatives of stilbene and styryl derivatives of stilbene; 4,4'-diamino-2,2'-stilbene disulfonic acid (flavonoids), 4,4'-distyryl biphenyl, methyl umbelliferone, coumarins, dihydroquinolinones, 1,3-diarylpyrazolines, naphthalimides, benzoxazoles, benzisoxazoles, benzimidazole systems, heterocyclic substituted pyrene derivatives, etc. Suitable brightener levels include lower levels of about 0.01 wt%, about 0.05 wt%, about 0.1 wt%, or even about 0.2 wt% to higher levels of 0.5 wt% or even 0.75 wt%.

[0028] In some embodiments of the present invention, the leveling agent is an acrylic leveling agent or a modified acrylic leveling agent, wherein the modified leveling agent is a fluorine-modified or phosphate-modified leveling agent.

[0029] In some embodiments of the present invention, the degassing agent includes wax powder and / or benzoin, which is used to remove air and eliminate bubbles.

[0030] The second aspect of the present invention proposes a method for preparing the super-amphiphobic carbon nanotube epoxy powder coating, comprising the following steps: mixing epoxy resin, curing agent, pigment filler and additives, then adding super-amphiphobic carbon nanotubes, extruding, tableting and grinding after mixing to obtain the super-amphiphobic carbon nanotube epoxy powder coating.

[0031] In some embodiments of the present invention, the preparation method of the super-amphiphobic carbon nanotube epoxy powder coating comprises the following steps: mixing epoxy resin, curing agent, pigments and additives for 0.5 to 24 hours, then adding super-amphiphobic carbon nanotubes, mixing for 6 to 12 hours, and then extruding, tableting and grinding to obtain the super-amphiphobic carbon nanotube epoxy powder coating.

[0032] The third aspect of the present invention provides a super-amphiphobic carbon nanotube epoxy powder coating, comprising the super-amphiphobic carbon nanotube epoxy powder coating.

[0033] In some embodiments of the present invention, the super-amphiphobic carbon nanotube epoxy powder coating is obtained by electrostatically spraying the super-amphiphobic carbon nanotube epoxy powder coating onto the surface of a metal substrate and curing it.

[0034] In some embodiments of the present invention, the process parameters of the electrostatic spraying are: electrostatic voltage is 60kV~70kV, the distance between the spray gun nozzle and the metal substrate is 10cm~20cm, the powder spraying angle is 70°~90°, and the powder spraying pressure is 0.4MPa~0.7MPa.

[0035] In some embodiments of the present invention, the curing temperature is 180° C. to 220° C., such as 190° C., 200° C., or 210° C.; and the curing time is 5 min to 20 min, such as 10 min or 15 min.

[0036] In some embodiments of the present invention, the thickness of the super-amphiphobic carbon nanotube epoxy powder coating is 25 to 65 μm.

[0037] The fourth aspect of the present invention provides an application of the super-amphiphobic carbon nanotube epoxy powder coating and / or the super-amphiphobic carbon nanotube epoxy powder coating in metal corrosion protection.

[0038] The beneficial effects of the present invention are:

[0039] (1) The present invention utilizes the abundant hydroxyl groups on the surface of carbon nanotubes to perform fluorination modification on the surface of carbon nanotubes, thereby obtaining extremely low surface energy. At the same time, the F element is very stable and can remain stable under long-term ultraviolet radiation, thus giving the carbon nanotubes strong weather resistance;

[0040] (2) The present invention uniformly mixes super-amphiphobic carbon nanotube powder with epoxy resin and curing agent to prepare super-amphiphobic carbon nanotube powder coating, and then prepares super-amphiphobic carbon nanotube powder coating on a metal substrate by electrostatic spraying and baking curing. The coating preparation process is simple and fast, and avoids the use of a large amount of solvents, which is in line with the development concept of saving and environmental protection;

[0041] (3) The carbon nanotube powder coating provided by the present invention has good weather resistance and wear resistance as shown in outdoor exposure tests, UV accelerated weathering tests and wear resistance tests, thereby achieving stronger and more lasting anti-corrosion performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the FTIR image of the carbon nanotubes in Example 4 of the present invention.

[0043] Figure 2 This is a Raman image of the carbon nanotubes in Example 4 of the present invention.

[0044] Figure 3 This is a thermogravimetric image of the carbon nanotubes in Example 4 of the present invention.

[0045] Figure 4This is the SEM of the surface structure of Example 4 of the present invention.

[0046] Figure 5 This is the SEM of the cross-sectional structure of Example 4 of the present invention.

[0047] Figure 6 The hydrophobic angle and the rolling angle of the embodiment of the present invention and the comparative example are shown in FIG.

[0048] Figure 7 It is the change of hydrophobic angle in the weathering experiment of the embodiment of the present invention, wherein a (water contact angle) and b (oil contact angle) are the changes of hydrophobic angle in the UV accelerated weathering test; c (water contact angle) and d (oil contact angle) are the changes of hydrophobic angle in the outdoor exposure test.

[0049] Figure 8 The changes of hydrophobic angle in the falling sand test (a), running water impact test (b), and weight wear test (c).

[0050] Fig. 9 The appearance changes of Example 4 (left) of the present invention and Comparative Example 1 (right) after 15 days of salt spray accelerated corrosion test.

[0051] Fig.10 It is the paraffin oil contact angle of Example 4 of the present invention.

[0052] Fig.11 It is the water contact angle of Example 4 of the present invention. DETAILED DESCRIPTION

[0053] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0054] The materials and instrument information involved in the implementation scheme of the present invention are as follows:

[0055] Hydroxylated carbon nanotubes were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0056] Epoxy resin 804, provided by China Petrochemical Corporation;

[0057] Phenolic curing agent 410M, provided by Huangshan Xinjia Fine Materials Co., Ltd.;

[0058] Titanium dioxide, provided by Zhongshan Huaxingong Material Technology Co., Ltd.;

[0059] Benzoin (degassing agent), provided by Zhongshan Huaxingong Material Technology Co., Ltd.;

[0060] Q235 standard steel (150 mm × 70 mm × 0.8 mm) was purchased from Jiangsu Guoqiang Galvanizing Industry Co., Ltd.;

[0061] Example 1

[0062] This embodiment prepares a coating, and the specific process is as follows:

[0063] (1) First, TEOS was dissolved in anhydrous ethanol, with a volume ratio of TEOS to anhydrous ethanol of 1:2, and ammonia water was added to adjust the pH to 14. A certain amount of carbon nanotubes was added thereto, and the mixture was reacted under magnetic stirring at room temperature for 18 h;

[0064] (2) adding perfluorooctyltrimethoxysilane to the mixed system obtained in step (1), with the volume ratio of fluorosilane to TEOS being 1:50, and continuing the reaction under magnetic stirring at room temperature for 6 hours;

[0065] (3) filtering the mixed system in step (2), drying, crushing, and sieving the obtained solid powder to obtain super-amphiphobic carbon nanotube powder;

[0066] (4) Weigh the super-amphiphobic carbon nanotube powder, epoxy resin, curing agent, pigment and filler obtained in step (3) in the proportions shown in Table 1;

[0067] (5) mixing epoxy resin, phenolic curing agent, titanium dioxide and benzoin uniformly, adding super-amphiphobic carbon nanotube powder, mixing uniformly, extruding, tableting, grinding and sieving to obtain super-amphiphobic carbon nanotube powder coating;

[0068] (6) The powder coating obtained in step (5) is electrostatically sprayed onto the surface of carbon steel. The process parameters of the electrostatic spraying are: the electrostatic voltage is 60 kV, the distance between the spray gun and the metal substrate is 15 cm, the powder spraying angle is 80°, the powder spraying pressure is 0.5 MPa, and then baked and cured at 220° C. for 10 min, and naturally cooled to obtain a super-amphiphobic carbon nanotube powder coating.

[0069] Example 2

[0070] This embodiment prepares a coating, and the specific process is as follows:

[0071] (1) First, TEOS was dissolved in anhydrous ethanol, with a volume ratio of TEOS to anhydrous ethanol of 1:2, and ammonia water was added to adjust the pH to 14. A certain amount of carbon nanotubes was added thereto, and the mixture was reacted under magnetic stirring at room temperature for 18 h;

[0072] (2) adding perfluorooctyltrimethoxysilane to the mixed system obtained in step (1), with the volume ratio of fluorosilane to TEOS being 1:50, and continuing the reaction under magnetic stirring at room temperature for 6 hours;

[0073] (3) filtering the mixed system in step (2), drying, crushing, and sieving the obtained solid powder to obtain super-amphiphobic carbon nanotube powder;

[0074] (4) Weigh the super-amphiphobic carbon nanotube powder, epoxy resin, curing agent, pigment and filler obtained in step (3) in the proportions shown in Table 1;

[0075] (5) mixing epoxy resin, phenolic curing agent, titanium dioxide and benzoin uniformly, adding super-amphiphobic carbon nanotube powder, mixing uniformly, extruding, tableting, grinding and sieving to obtain super-amphiphobic carbon nanotube powder coating;

[0076] (6) The powder coating obtained in step (5) is electrostatically sprayed onto the surface of carbon steel. The process parameters of the electrostatic spraying are: the electrostatic voltage is 60 kV, the distance between the spray gun and the metal substrate is 15 cm, the powder spraying angle is 80°, the powder spraying pressure is 0.5 MPa, and then baked and cured at 220° C. for 10 min, and naturally cooled to obtain a super-amphiphobic carbon nanotube powder coating.

[0077] Example 3

[0078] This embodiment prepares a coating, and the specific process is as follows:

[0079] (1) First, TEOS was dissolved in anhydrous ethanol, with a volume ratio of TEOS to anhydrous ethanol of 1:2, and ammonia water was added to adjust the pH to 14. A certain amount of carbon nanotubes was added thereto, and the mixture was reacted under magnetic stirring at room temperature for 18 h;

[0080] (2) adding perfluorooctyltrimethoxysilane to the mixed system obtained in step (1), with the volume ratio of fluorosilane to TEOS being 1:50, and continuing the reaction under magnetic stirring at room temperature for 6 hours;

[0081] (3) filtering the mixed system in step (2), drying, crushing, and sieving the obtained solid powder to obtain super-amphiphobic carbon nanotube powder;

[0082] (4) Weigh the super-amphiphobic carbon nanotube powder, epoxy resin, curing agent, pigment and filler obtained in step (3) in the proportions shown in Table 1;

[0083] (5) mixing the above-mentioned epoxy resin, phenolic curing agent, titanium dioxide and benzoin in the above-mentioned amounts by weight, adding the super-amphiphobic carbon nanotube powder, stirring evenly, extruding, tableting, grinding and sieving to obtain a super-amphiphobic carbon nanotube powder coating;

[0084] (6) The powder coating obtained in step (5) is electrostatically sprayed onto the surface of carbon steel. The process parameters of the electrostatic spraying are: the electrostatic voltage is 60 kV, the distance between the spray gun and the metal substrate is 15 cm, the powder spraying angle is 80°, the powder spraying pressure is 0.5 MPa, and then baked and cured at 220° C. for 10 min, and naturally cooled to obtain a super-amphiphobic carbon nanotube / epoxy powder coating.

[0085] Example 4

[0086] This embodiment prepares a coating, and the specific process is as follows:

[0087] (1) First, TEOS was dissolved in anhydrous ethanol, with a volume ratio of TEOS to anhydrous ethanol of 1:2, and ammonia water was added to adjust the pH to 14. A certain amount of carbon nanotubes was added thereto, and the mixture was reacted under magnetic stirring at room temperature for 18 h;

[0088] (2) adding perfluorooctyltrimethoxysilane to the mixed system obtained in step (1), with the volume ratio of fluorosilane to TEOS being 1:50, and continuing the reaction under magnetic stirring at room temperature for 6 hours;

[0089] (3) filtering the mixed system in step (2), drying, crushing, and sieving the obtained solid powder to obtain super-amphiphobic carbon nanotube powder;

[0090] (4) Weigh the super-amphiphobic carbon nanotube powder, epoxy resin, curing agent, pigment and filler obtained in step (3) in the proportions shown in Table 1;

[0091] (5) mixing the above-mentioned epoxy resin, phenolic curing agent, titanium dioxide and benzoin in the above-mentioned amounts by weight, adding the super-amphiphobic carbon nanotube powder, stirring evenly, extruding, tableting, grinding and sieving to obtain a super-amphiphobic carbon nanotube powder coating;

[0092] (6) The powder coating obtained in step (5) is electrostatically sprayed onto the surface of carbon steel. The process parameters of the electrostatic spraying are: the electrostatic voltage is 60 kV, the distance between the spray gun and the metal substrate is 15 cm, the powder spraying angle is 80°, the powder spraying pressure is 0.5 MPa, and then baked and cured at 220° C. for 10 min, and naturally cooled to obtain a super-amphiphobic carbon nanotube / epoxy powder coating.

[0093] Comparative Example 1

[0094] This comparative example prepared a coating, and the specific process was as follows:

[0095] (1) Weigh the epoxy resin, curing agent, pigments and fillers according to the mass ratio shown in Table 1;

[0096] (2) mixing the epoxy resin, phenolic curing agent, titanium dioxide and benzoin in the above-mentioned amounts by weight, and then extruding, tableting, grinding and sieving to obtain an epoxy powder coating;

[0097] (3) The powder coating obtained in step (2) is electrostatically sprayed onto the surface of carbon steel. The process parameters of the electrostatic spraying are: the electrostatic voltage is 60 kV, the distance between the spray gun and the metal substrate is 15 cm, the powder spraying angle is 80°, the powder spraying pressure is 0.5 MPa, and then baked and cured at 220° C. for 10 min, and naturally cooled to obtain the epoxy powder coating.

[0098] Comparative Example 2

[0099] This comparative example prepares a coating, which is different from Example 1 in that the curing agent is polyetheramine, and the preparation method is the same as that of Example 1.

[0100] Table 1: Mass proportion of coating components in the examples and comparative examples

[0101] Components Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Epoxy resin 100 100 100 100 100 100 Superamphiphobic carbon nanotubes 2 4 6 8 - 2 Phenolic curing agent 25 25 25 25 25 25(Polyetheramine) Titanium dioxide 50 50 50 50 50 50 Benzoin 2 2 2 2 2 2

[0102] Test Example 1

[0103] In this test example, the coatings prepared in the embodiment and the comparative example were tested, and the results are shown in the figures.

[0104] from Figure 1 It can be observed that the modified carbon nanotubes have an obvious CF peak, indicating that the F element is fully grafted onto the surface of the carbon nanotubes. Figure 2 It is shown in the figure that the material is a carbon nanotube with an obvious flaky graphite structure. Figure 3 The carbon-silicon ratio in the modified carbon nanotubes was elucidated by combustion decomposition in an oxygen atmosphere.

[0105] Figure 4 , Figure 5 The SEM of the surface and cross-sectional structure of Example 4 shows that the coating thickness is about 40 μm and obvious short rod-shaped carbon nanotubes can be observed on the surface.

[0106] Figure 6 The hydrophobic angle and the rolling angle of the embodiment and the comparative example are shown in FIG. 1 . It can be seen that the super-amphiphobic property of the coating changes with the addition amount of carbon nanotubes, indicating that the prepared super-amphiphobic carbon nanotubes can significantly enhance the amphiphobic property of the coating.

[0107] Figure 7 (a, c) are the ultraviolet accelerated weathering test carried out in Example 4 under laboratory conditions (the temperature is constant at 25°C, the ultraviolet irradiation power is 0.78 W, and the contact angle of the coating is recorded every 100 hours). The relationship between the hydrophobic angle and time shows that the prepared super-amphiphobic coating can withstand 1000 hours of ultraviolet irradiation and still maintain super-amphiphobic performance.

[0108] Figure 7 (b, d) is placed under outdoor conditions for Example 4, and the contact angle of super double-repellent epoxy composite powder coating is tested every 1 month. Outdoor environment is Guangzhou, and Guangzhou climate belongs to the southern subtropical monsoon marine climate zone, and it is hot, humid and rainy all year round and is near the sea, and Guangzhou has rapid economic development and developed industry, so that Guangzhou is displayed as a unique high temperature, acid rain, high salt industrial and marine comprehensive atmospheric corrosion environment, and the atmospheric corrosion environment grade is C3 level. It can be seen that the prepared super double-repellent coating can still have stable super double-repellent performance after experiencing six months of outdoor exposure.

[0109] Figure 8 For Example 4, a falling sand test (the prepared coating sample was placed on the test bench at an angle of 45°, and standard test sand was dropped from a height of 100 cm. The contact angle of the coating surface was measured every time 10 g of test sand was dropped to simulate the condition of the coating being eroded by wind and sand in the actual use environment, which was used to judge the wear resistance and impact resistance of the coating) and a flowing water impact test (the prepared coating sample was placed on the test bench at an angle of 45°, and the coating surface was impacted with a water flow rate of 9 L / min, and the contact angle of the coating surface was measured every 1 min. To simulate the conditions of being washed by rain in the actual use environment, it is used to judge the stability of the coating), 200g weight wear test (a weight of 200g is loaded on the back of the coating, and then it is placed on the sandpaper surface, where the coating surface is in direct contact with the sandpaper surface. The sample is then pushed along the sandpaper surface for 10cm, and then pushed in the opposite direction for 10cm. After reciprocating friction, the contact angle of the sample after different wear cycles is recorded to judge its wear resistance), and the change in the hydrophobic angle after different wear modes is demonstrated. The prepared super-amphiphobic coating has excellent wear resistance.

[0110] Fig. 9 The appearance changes after the comparative example 1 and the example 4 were subjected to a 15-day salt spray accelerated corrosion test (according to the requirements of GB / T 10125-2012, the coating was sprayed on a Q235 steel plate, and the sample was tilted into a salt spray test box, the temperature was 35±2°C, the spray volume was 1mL / (80cm2), the salt spray solution was a 5wt% NaCl solution, and the surface corrosion of the coating was observed at intervals of 5 days) can be seen by observing the width of the corrosion marks. The prepared super-amphiphobic coating has excellent salt spray corrosion resistance.

[0111] Fig.10 , Fig.11 The test results of the paraffin oil contact angle and water contact angle of Example 4 show that the oil contact angle and water contact angle of the coating are 153° and 158° respectively.

[0112] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A super-amphiphobic carbon nanotube epoxy powder coating, characterized in that: The raw materials for its preparation include the following components in parts by mass: Epoxy resin: 80 to 120 parts; Super amphiphobic carbon nanotubes: 1 to 50 parts; Curing agent: 10 to 50 parts; Pigments and fillers: 10 to 100 parts; Additives: 2 to 20 parts; The super-amphiphobic carbon nanotubes include carbon nanotubes loaded with silicon dioxide and then modified with fluorosilane.

2. The super-amphiphobic carbon nanotube epoxy powder coating according to claim 1, characterized in that: The super-amphiphobic carbon nanotubes are prepared by mixing hydroxylated carbon nanotubes with a silicon source and then subjecting the mixture to a fluorosilane modification treatment.

3. The super-amphiphobic carbon nanotube epoxy powder coating according to claim 1, characterized in that: The fluorosilane includes at least one of perfluorooctyltrimethoxysilane, perfluorooctyltriethoxysilane and perfluorododecyltrimethoxysilane.

4. The super-amphiphobic carbon nanotube epoxy powder coating according to claim 1, characterized in that: The epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin.

5. The super-amphiphobic carbon nanotube epoxy powder coating according to claim 1, characterized in that: The curing agent is at least one of a dicyandiamide curing agent, a phenol curing agent, and an acid anhydride curing agent.

6. A method for preparing the super-amphiphobic carbon nanotube epoxy powder coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: After epoxy resin, curing agent, pigments and fillers and additives are mixed, super-amphiphobic carbon nanotubes are added, mixed, extruded, tableted and ground into powder to obtain the super-amphiphobic carbon nanotube epoxy powder coating.

7. A super-amphiphobic carbon nanotube epoxy powder coating, characterized in that: The invention comprises the super-amphiphobic carbon nanotube epoxy powder coating as described in any one of claims 1 to 5.

8. The super-amphiphobic carbon nanotube epoxy powder coating according to claim 7, characterized in that: The super-amphiphobic carbon nanotube epoxy powder coating comprises electrostatically spraying the super-amphiphobic carbon nanotube epoxy powder coating onto the surface of a metal substrate and curing the coating.

9. The super-amphiphobic carbon nanotube epoxy powder coating according to claim 7, characterized in that: The thickness of the super-amphiphobic carbon nanotube epoxy powder coating is 25-65 μm.

10. Use of the super-amphiphobic carbon nanotube epoxy powder coating according to any one of claims 1 to 5 and / or the super-amphiphobic carbon nanotube epoxy powder coating according to any one of claims 7 to 9 in metal corrosion protection.

Citation Information

Patent Citations

  • Preparation method of acrylic resin finishing agent modified by nano silicon dioxide (SiO2)-coated multi-walled carbon nanotubes

    CN102786644A

  • Superhydrophobic powder coating, and preparation method and application thereof

    CN107652795A

  • Wear-resistant super-hydrophobic paper and preparation method thereof

    CN109440525A

  • Superhydrophobic transparent conductive paper and preparation method thereof

    CN109468874A

  • Super-hydrophobic coating and preparation method and application thereof, and super-hydrophobic coating and preparation method and application thereof

    CN114106676A